The Position Of Correctional Institutions In Providing Guidance To Prisoners In Indonesia - I Ketut Sukadana; Leni Dwi Nurmala; Nurwita Ismail (International Journal of Law and Society, 2024)
A correctional institution is a place that has the function of providing training for prisoners to carry out what the court has decided for them. The end of the judicial settlement process lies with the Correctional Institution, whether or not the criminal justice objectives are successful can be seen from the results that have been achieved and issued by the correctional institution in the entire criminal justice process. The type of research used is normative research, namely normative legal research or library research. The position of Correctional Institutions (Lapas) is as the final sub-system which directly deals with prisoners to carry out guidance. Tasked with providing community guidance and community services, guidance for correctional clients in accordance with applicable laws and regulations as well as rehabilitation and resocialization of law violators, even to crime prevention. The Role of Correctional Institutions in Indonesia is Linked to the Purpose of Punishment. The existence of correctional institutions in Indonesia carries out three very important roles, namely: carrying out law enforcement, the role of coaching and internal strengthening of correctional institutions. The suggestion that the author puts forward is that the government should provide the facilities and infrastructure needed by correctional institutions to develop correctional inmates with the aim of returning correctional inmates to society so that they can live independently and be useful in society. So that correctional institutions can increase their role and function effectively in providing guidance to inmates.